1980
DOI: 10.1071/bi9800105
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Modes of Selection on the Alcohol Dehydrogenase Locus in Drosophila Melanogaster

Abstract: Three experiments have been carried out which show that exogenous environments of ethanol impose selection on the alcohol dehydrogenase (Adh) locus of D. melanogaster. This locus is widely polymorphic for two alleles, AdhF and Adhs, and AdhF generally produces about twice as much alcohol dehydrogenase activity as Adhs. In the first experiment, AdhF IAdhF and AdhF/Adhs flies survived equally often and Adhs/Adhs flies less frequently after exposure for 7 days to medium impregnated with ethanol. The same pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In experiments where survival in ethanol-supplemented food or exposure to medium impregnated with ethanol is used, the usual situation is that FF has the highest survival which correlates positively with ADH activity (Gibson, 1970;Day et al, 1974;Oakeshott et al, 1980). In addition, Thompson & Kaiser (1977) demonstrated for two strains differing in ADH activity that the strain with the highest activity also shows the highest egg-to-adult survival on food supplemented with alcohols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments where survival in ethanol-supplemented food or exposure to medium impregnated with ethanol is used, the usual situation is that FF has the highest survival which correlates positively with ADH activity (Gibson, 1970;Day et al, 1974;Oakeshott et al, 1980). In addition, Thompson & Kaiser (1977) demonstrated for two strains differing in ADH activity that the strain with the highest activity also shows the highest egg-to-adult survival on food supplemented with alcohols.…”
Section: Discussionmentioning
confidence: 99%
“…1), although the heterozygote FS complicates the issue being close to SS for ethanol tolerance and between the two homozygotes for enzyme activity. Oakeshott et al (1980) studied adult survival of the three Adh genotypes exposed to ethanol vapour for 45 min and found that the SS flies survived the treatment better than FF flies as in the experiments under discussion, where exposure was in terms of days rather than minutes. In our experiments, the only energy source provided is ethanol, which is normally converted to acetic acid via acetaldehyde (Deltombe-Lietaert et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the 2 common alleles at the Adh locus of D. melanogaster differ by a single base substitution (K REITMAN , 1983). This difference has affected the ability of individuals to utilize ethanol-rich environments, at least in the laboratory (V AN D E i.oEN et al, 1978 ;O AKESHOTT et al, 1980). Field studies are essential in the detection of selective factors affecting enzyme polymorphisms (C LARKE , 1975).…”
Section: Introductionmentioning
confidence: 97%
“…One of the most suitable systems for such an examination is the polymorphic Odh locus. Series of experiments were set up to study the connection between the "alcohol tolerance and the frequency changes at the Adh locus (Bijlsma-Meeles & Van Delden, 1974;Dorado & Barbancho, 1984;Oakeshott et al, 1980;Sanchez-Canete et al, 1986;Wilson et al, 1982;Van Delden, 1982;Van Herrewege &David, 1980 andVigue et al, 1982). However, few articles have been published on the frequency changes at the Odh locus as an effect of alcoholic stress Nichols, 1971 andWills et al, 1975).…”
Section: Introductionmentioning
confidence: 99%